Yeast-fermented feed improves high-concentrate diet-induced mastitis in dairy goats by regulating rumen microbiota - Wu, Keyi; Sun, Xiaochun; Xu, Jiawen; Guan, Zhihang; Yuan, Weijie; Bao, Lijuan; Zhao, Yihong; Shan, Ruping; Chen, Hui; Zhao, Caijun; Hu, Xiaoyu; Fu, Yunhe; et al. (Frontiers in Microbiology, 2025)
Mastitis is a crucial disease that restricts the development of the dairy industry. In production practice, long-term high-concentrate diet (HCD) is often employed to boost milk yield. However, this can lead to rumen microbiota disorder and eventually results in mastitis. Microbial fermented feed has drawn increasing attention due to its abundant functions, safety, and effectiveness. Yeast, as a widely used fungus, has excellent fermentation performance and a variety of beneficial physiological functions. In this study, we investigated the therapeutic effect of yeast fermented feed (YFF) on mastitis in dairy goats induced by ruminal dysbiosis. Twenty-four dairy goats in late lactation, with an initial body weight of 34.65 ± 5.46 kg, were selected for the study. The total experimental period lasted 55 days. In the control group, a roughage-to-concentrate ratio (F:C) of 7:3 was consistently provided. For the subacute ruminal acidosis (SARA) group, eight dairy goats were given a 5:5 F:C diet free of charge for 10 days prior to the start of the experiment to ensure their adaptation to the diet. Subsequently, these eight dairy goats were fed an HCD consisting of 30% roughage and 70% mixed concentrate until the end of the experiment. For the SARA+Y group, eight dairy goats were fed the same diet as the SARA group from the beginning of the experiment until day 45. After that, 80 to 100 grams of YFF per goat were added to the diet daily for 10 days until the end of the experiment. In this study, adding YFF on the basis of HCD alleviated mastitis by restoring the function of the rumen barrier and regulating the imbalance of rumen microbiota. It alleviated the symptoms of SARA, reduced the levels of LPS in the rumen, serum, and mammary glands, and reduced the levels of proinflammatory cytokines. Specifically, it was reflected in restoring the function of the blood-milk barrier, limiting the inflammatory response, and reducing oxidative stress. In conclusion, these results suggest that supplementation with YFF alleviates mastitis induced by ruminal microbiota disturbance due to feeding HCD in several ways. This finding paves the way for a new approach and method to address mastitis in ruminant animals. It not only helps enhance the health level of ruminants but also plays a positive role in improving breeding efficiency. At the same time, it provides a strong guarantee for enhancing the quality of dairy products and lays a solid foundation for the sustainable development of the dairy industry.